Efektivitas Metode Pembelajaran Daring terhadap Peningkatan Kinerja dan Kompetensi ASN, Studi Kasus di RSUP Dr. Sitanala Tangerang - Hastuti, Ade Dewi; Tamyiz, Fauzul Abdurrahman; Puspaningrum, Florentina Endah (Universitas Mercu Buana, 2025)
This study aims to analyze the effectiveness of online learning methods in improving the performance and competence of Civil Servants (ASN), using a case study at RSUP Dr. Sitanala Tangerang, with a focus on regulatory frameworks and learning theories. The research method used is literature study by collecting and analyzing data on online learning practices at RSUP Dr. Sitanala and from laws and regulations, policy documents, and expert theories related to online learning and knowledge management. The results show that online learning has great potential to improve ASN competence, especially in terms of time efficiency and accessibility. However, its effectiveness depends heavily on motivational support from management, technological support, and ongoing evaluation. Regulatory frameworks such as Government Regulation No. 17 of 2020 and Minister of Health Regulation No. 20 of 2014 emphasize the importance of developing ASN competence through modern methods, including online learning.